Analysis of the Influence of Selecting Project Implementation Methods on Project Success: Case Study of Competency Certificate Reminder Feature Development at PT Eleska Iatki - Mulyati, Rika; Suakanto, Sinung; Raharjo, Adi; Agustien, Ferry; Priyadi, Djoko (SemanTIK : Teknik Informasi, 2024)
Project success relies on effective management and efficient implementation methods. These methods optimize potential, overcome risks, develop timely plans, maintain quality, and manage budgets. A correlation analysis was conducted on four attributes: clarity, accuracy, effectiveness, selection of methods, and standard methods. The results showed a high correlation between project implementation methods and project success, indicating a significant impact on project success. PT Eleska Iatki, a business process provider, requires digital projects for competency certificate validity period reminders, emphasizing the importance of appropriate implementation methods for project success and company goals. Keywords; Project Management, Implementation Methods, Correlation, Chi-Square, Data Analysis